On the treatment of super-heavy syllables in Arabic Dialects: an Optimality Theoretic approach to historical typology - Bokhari, Hassan (Papers in Historical Phonology, 2021)
This study provides a historical typological Optimality Theoretic analysis of the treatment of potential super-heavy syllables in six Arabic varieties: Hijazi, Egyptian, Emirati, Kuwaiti, Algerian, and Palestinian. The analysis in this study uses the same violable OT constraints for all languages, and the differences between the grammars are represented by the order in which the constraints are ranked relative to one another. The similarities and differences between these varieties are examined from the point of view of one approach to historical OT (Cho 1998), which states that individual pairs of constraints may be ranked or unranked in relation to one another, one operation at a time, meaning that switching the order of two constraints takes two steps historically. According to Cho (1998, 45), “each step of a sound change should be viewed as a change in the ranking of constraints.” Cho’s approach in detecting the historical typological differences between varieties by counting the steps of constraint reranking is compatible with a common approach to historical linguistics. Specifically, Wichmann et al. (2010) provide a quantitative method for determining the geographic homeland of a group of related languages, which takes into account a simple linguistic-difference metric and the geographic distance between the languages. Using constraint reranking in place of Wichmann et al.’s linguistic-difference metric to calculate the homeland of Arabic dialects results in an area around Hijaz as the homeland of Arabic dialects, since Hijazi, Egyptian and Emirati dialects form a cluster of geographically close, but linguistically diverse dialects.